Health care institution target management under the conditions of public-private partnership implementation - Chopchik, V. D.; Kanyura, O. A. (Journal of Education, Health and Sport, 2019)
The objective: to substantiate the methodological approaches to the target management (TM) of a health care institution (HCI) in the context of the implementation of public-private partnership (PPP). Materials and methods. General scientific methods of analysis, synthesis, interpretation of scientific data, as well as systemic and structural-functional approaches were used in the work. Results. The article developed methodological approaches to HCI’s TM in the context of PPP, the features of using the system of target indicators are presented, a scheme for improving the production efficiency of medical activities, an informative map of indicators and methods for monitoring, calculating and analyzing individual targets is given. Conclusions. Formation of TM mechanisms is the priority direction for the development of HCI in the context of PPP. Implementation of TM will provide employees with a deeper understanding of an organization and its divisions aims, and consequently, a more conscientious fulfillment of their duties, improve interaction in the management system and enable subordinates to have more powers, clarify existing norms and standards and create conditions for a more objective control and encouragement of workers, and as a result, will increase the effectiveness of HCI.